2021
DOI: 10.1021/acsaem.1c03170
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Conductive Frameworks and Metal Catalytic Sites Derived from Cross-Linked Porous Porphyrin-Based Polyimides for Enhanced Conversion of Lithium Polysulfides in Li–S Batteries

Abstract: Shuttling behavior of lithium polysulfides (LiPSs) resulting from insufficient adsorption capacity, delayed diffusion, and sluggish catalytic kinetics severely hampers further exploitation of lithium−sulfur (Li−S) batteries. A reasonable and optimized composition of the cathodic host in Li−S batteries is an efficient approach to utilize polysulfides and impede their loss. The combination of the factors preferable porosity parameters, efficient electrical framework, and intrinsic catalytic sites achieves the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The introduction of metals in carbon-based materials or the use of metal compounds is the typical way to improve the electrochemical performance of Li-S batteries. The non-polar carbon-based host materials interact with LiPSs via weak van der Waals force, while metals and metal compounds can chemically adsorb LiPSs by forming M-S (M: metal) bonds [30] . Compared with the weak van der Waals force, the M-S bonds are stronger, and the inhibition of the shuttle effect is more effective.…”
Section: Metals and Metal Compoundsmentioning
confidence: 99%
“…The introduction of metals in carbon-based materials or the use of metal compounds is the typical way to improve the electrochemical performance of Li-S batteries. The non-polar carbon-based host materials interact with LiPSs via weak van der Waals force, while metals and metal compounds can chemically adsorb LiPSs by forming M-S (M: metal) bonds [30] . Compared with the weak van der Waals force, the M-S bonds are stronger, and the inhibition of the shuttle effect is more effective.…”
Section: Metals and Metal Compoundsmentioning
confidence: 99%
“…31,32 In addition, fringe benefits can be offered and the catalytic performance of metals can be enhanced since carbon-based materials usually possess good electric conductivities and adsorption affinities. 33 Our previous study found that using a chelating agent as the raw material can promote the degree of dispersion of metal particles through one-step thermal decomposition preparation. 34 Co-incorporated N-doped porous carbon (CFO/ Fe@C) was successfully prepared using EDTA, Fe salt and Co salt as the starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 In addition, fringe benefits can be offered and the catalytic performance of metals can be enhanced since carbon-based materials usually possess good electric conductivities and adsorption affinities. 33…”
Section: Introductionmentioning
confidence: 99%